Thermal pulse inspection of multilayer parts; The Soviet journal of nondestructive testing; Vol. 20, iss. 6 - Ivanov A. I. (1984, 1984)
A thermal inspection method based on thermal pulse heating of a part and recording the temperature at the back side of the part is described. It is suggested that the time required for the temperature to reach certain predetermined levels be used as the defectiveness criterion. The experimental results for bonded and welded parts are given. A method for calculating the basic parameters of thermal pulse inspection (TPI) systems for checking integral changes in thermal diffusivity with respect to the amplitude and time criteria is proposed.